Thymectomy lowers the myasthenia gravis biomarker miR-150-5p - Molin, Carl Johan; Sabre, Liis; Weis, Cleo-Aron Thias; Punga, Tanel; Punga, Anna Rostedt (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2018)
Objective: The aim of the study was to analyze the effect of thymectomy on the proposed disease-specific microRNA (miRNA) biomarkers miR-150-5p and miR-21-5p in patients from the prospective randomized trial of thymectomy in myasthenia gravis (MGTX trial) and to evaluate the longitudinal changes in clinical patterns compared with these miRNA levels. - Methods: Serum samples were obtained from 80 patients with MG who were included in the MGTX trial. Thirty-eight patients were randomized to thymectomy plus prednisone treatment, and 42 patients were randomized to prednisone treatment. Serum samples were analyzed for the expression of miR-150-5p and miR-21-5p, with quantitative reverse transcriptase PCR at baseline and at 12, 24, and 36 months after randomization. The inclusion criteria for participation in the MGTX trial were age 18-65 years, generalized myasthenia gravis (Myasthenia Gravis Foundation of America Class II-IV), disease duration of less than 5 years, and seropositivity for acetylcholine receptor antibodies (AChR+). - Results: Patients treated with thymectomy had lower levels of miR-150-5p at 24 months, both compared with baseline values (p = 0.0011) and the prednisone group (p = 0.04). No change in miRNA levels was found in the prednisone group. Levels of miR-21-5p displayed a negative correlation with the prednisone dose within the prednisone-only group (p ≤ 0.001). - Conclusions: Thymectomy lowers the levels of the proposed biomarker miR-150-5p, which strengthens its position as a potential disease-specific biomarker for AChR+ MG.